2021
DOI: 10.1152/ajpheart.00542.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of ventricular repolarization time following abrupt changes in heart rate: comparisons and reproducibility of repeated atrial and ventricular pacing

Abstract: Adequate adaptation of ventricular repolarization (VR) duration to changes in heart rate (HR) is important for cardiac electromechanical function and electrical stability. We studied the QT and QTpeak adaptation in response to abrupt start and stop of atrial and ventricular pacing on two occasions with at least one month's interval in 25 study subjects with permanent pacemakers. Frank vectorcardiography was used for data collection. Atrial or ventricular pacing was performed for 8 minutes aiming at a cycle len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Our observation of, on average, slower hysteresis speed during heart rate acceleration contradicts a recent report by Axelsson et al (2021) who observed the opposite. Nevertheless, they investigated the phenomenon in patients with permanent pacemakers and, thus, abnormalities in cardiac electrophysiology in whom QT/RR hysteresis might be different to that in the healthy subjects who were investigated in this study.…”
Section: Qt/rr Hysteresis Propertiescontrasting
confidence: 99%
“…Our observation of, on average, slower hysteresis speed during heart rate acceleration contradicts a recent report by Axelsson et al (2021) who observed the opposite. Nevertheless, they investigated the phenomenon in patients with permanent pacemakers and, thus, abnormalities in cardiac electrophysiology in whom QT/RR hysteresis might be different to that in the healthy subjects who were investigated in this study.…”
Section: Qt/rr Hysteresis Propertiescontrasting
confidence: 99%
“…The hysteresis of QT adaptation to HR change has been studied in several reports by investigating the QT/RR relationship during exercise testing or from Holter recordings, applying different measures of hysteresis with conflicting results as reviewed recently (Gravel et al, 2018 ). Differences between studies may at least in part be due to the well‐known difference in hysteresis when increasing versus decreasing the HR, faster in the former as shown also in humans (Seethala et al, 2011 ; Axelsson et al, 2021 ). This essential feature of QT hysteresis was pointed out (together with other limitations) in one previous very thorough QT/RR study (Malik et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although atrial and ventricular pacing result in similar dynamics in QT hysteresis, ventricular pacing induces potentially confounding repolarization changes related to ventricular activation‐induced short‐term cardiac memory, at least when ventricular pacing lasts 8 minutes or more (Axelsson et al, 2021 ; Rosen & Bergfeldt, 2015 ). Incremental atrial pacing is presumably most physiological and was applied in one of our previous studies on patients with supraventricular tachycardia but otherwise healthy undergoing heart catheterization for ablation therapy (Axelsson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the heart rate is fast, the ventricular repolarization period is shortened while significantly prolonged when the heart rate is slow [3,4]. This kind of frequency adaptability of ventricular repolarization which is called ventricular repolarization reserve, also known as ventricular repolarization adaptability, is of great significance to the automatic regulation and effectiveness of ventricular contraction and relaxation under physiological conditions [5,6]. In recent years, evidences have shown that the inward late sodium current in the plateau phase of cell membrane plays a key role in the frequency adaptation of ventricular repolarization [7][8][9].…”
Section: Introductionmentioning
confidence: 99%